Konieczność zastosowania metod mikrochirurgicznych i monitoringu śródoperacyjnego w patologii kanału stępu. Technika zabiegu - Andrychowski, Jarosław; Koziel, Dorota; Szczepanowska-Wolowiec, Beata; Dzięgiel, Krzysztof (Medical Studies/Studia Medyczne, 2020)
A Schwannoma tumour located in the posterior tibial nerve in the tarsal tunnel is extremely rare [1–10], and hence surgery of this pathology also occurs rarely. Schwannoma within the foot, causing pain syndrome, requires differentiation from Morton’s metatarsalgia [11]. There are several such cases of surgeries during the 20-year period described in the literature, but intraoperative monitoring techniques and microsurgery are still only an option. Due to the anatomical relationship, nerve vascular supply [12–15] and muscle functions innervated by the tibial nerve, related to the support, foot arch, and effect on the movement pattern [16, 17]. The surgical technique should use methods of microsurgical dissection and intraoperative neurophysiological monitoring in order to ensure safe surgery.